2005
DOI: 10.1038/sj.bjc.6602736
|View full text |Cite
|
Sign up to set email alerts
|

Cervical human papillomavirus infection and squamous intraepithelial lesions in rural Gambia, West Africa: viral sequence analysis and epidemiology

Abstract: The development of effective strategies against cervical cancer in Africa requires accurate type specific data on human papillomavirus (HPV) prevalence, including determination of DNA sequences in order to maximise local vaccine efficacy. We have investigated cervical HPV infection and squamous intraepithelial lesions (SIL) in an unselected cohort of 1061 women in a rural Gambian community. Squamous intraepithelial lesions was diagnosed using cytology and histology, HPV was typed by PCR-ELISA of DNA extracts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 62 publications
6
44
2
Order By: Relevance
“…Human papillomavirus-52, HPV-35, and HPV-58 were the most prevalent types in the present study. A high prevalence of these HPV types has been also observed in other African studies (Gravitt et al, 2000;Castellsague et al, 2001;De Vuyst et al, 2003;Mayaud et al, 2003;Xi et al, 2003;Baay et al, 2004;Thomas et al, 2004;Wall et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Human papillomavirus-52, HPV-35, and HPV-58 were the most prevalent types in the present study. A high prevalence of these HPV types has been also observed in other African studies (Gravitt et al, 2000;Castellsague et al, 2001;De Vuyst et al, 2003;Mayaud et al, 2003;Xi et al, 2003;Baay et al, 2004;Thomas et al, 2004;Wall et al, 2005).…”
Section: Discussionsupporting
confidence: 73%
“…While the epidemiology of genital HPV types has been relatively better studied in Southern and Eastern African countries such as Kenya (Temmerman et al, 1999;De Vuyst et al, 2003), Malawi (Miotti et al, 1996), Mozambique (Castellsague et al, 2001), Tanzania (Mayaud et al, 2003), Uganda (Serwadda et al, 1999), and Zimbabwe (Gravitt et al, 2002;Baay et al, 2004), data from Western Africa have been scarce. The prevalence of HPV infection and associated cervical lesions have been studied in Ivory Coast (La Ruche et al, 1998) and Mali (Bayo et al, 2002), but detailed HPV types were only reported from Senegal (Xi et al, 2003), Nigeria (Thomas et al, 2004), and The Gambia (Wall et al, 2005). Prevalence rates of HPV infection ranging from 13 to 40% have been reported from low-risk or general populations of sub-Saharan African countries (Miotti et al, 1996;Temmerman et al, 1999;Castellsague et al, 2001;De Vuyst et al, 2003;Mayaud et al, 2003;Xi et al, 2003;Baay et al, 2004;Thomas et al, 2004;Wall et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, comparison of our data with the Scottish cohort identified an overall lower percentage of HPV 16, HPV 18, HPV 31, HPV 51, HPV 52 and HPV 68 and an increase in HPV 35, HPV 66 and LR-HPV types. The high incidence of HPV 35 has been reported in other papers using the PCR-EIA method of Walboomers et al (Wall et al, 2005) and future work will investigate this further. …”
Section: Hpv Prevalencementioning
confidence: 52%